Water mites of the family Aturidae Thor, 1900 from Turkey (Acari: Hydrachnidia), with description of two new species - Esen, Yunus; Pesic, Vladimir; Erman, Orhan (Magnolia Press, 2011)
This paper deals with the water mite species of the family Aturidae Thor, collected from running waters in Bingol Province, Turkey. Javalbia (Javalbicula) turcica sp. nov. and Barbaxonella bingolensis sp. nov. are described as new species; Axonopsis armata Chaudonneret & Angelier, 1949 is synonymized with A. romijni Viets, 1923; Kongsbergia (Kongsbergia) persica Pesic, 2005, Albaxona lundbladi Motas & Tanasachi, 1947, Axonopsis (Hexaxonopsis) romijni Viets, 1923, A. (Navinaxonopsis) persica Pesic, 2004 and A. (Paraxonopsis) vietsi Motas & Tanasachi, 1947 are reported for the first time for Turkey.
Keywords: Water mites; running waters; Bingol Province; Turkey; Aturidae